Living Under the Same Roof Before the Date of Separation: The Relevance of Maqāṣid al-Sharī’ah and Minangkabaunese Custom in A New Direction for Families - Nofiardi Nofiardi; Fahmil Samiran (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Minangkabau community is known for its matrilineal kinship, in which a husband after the marriage lives with his wife’s family. If there are constant quarrels in the marriage and it is difficult to continue the marriage, the husband who leaves his wife’s house will not return unless he is taken back according to custom by his wife’s family. Yet, if divorce should be the final decision, then the husband must also leave the house until the judge decides it. This research aimed at exploring the notion of living together under the same roof before the date of separation or divorce process, a new direction for families in the Minangkabau community with maqāṣid al-sharī’ah approach. A qualitative approach was used to conduct this study. The data were obtained through documentation and interviews. The documents were the decision of the Batusangkar Religious Court that were appealed to the West Sumatra High Religious Court. Meanwhile, the interviewees were the judges of the courts. The maqāṣid al-sharī’ah approach was used to analyze a very interesting decision made for a divorce case occurred in Luhak Tanah Datar area. The results showed that differences in the understanding of Maqāṣid al-sharī’ah influenced decisions and indicated new directions in the families of the Minangkabau community.